Tecnologias na educação matemática: o uso da HP 12 C na resolução de problemas em Matemática financeira com alunos do 3° ano do ensino médio - Penha, Marcelo da Silva (2020)
The objective of this study is to present, in a clear way, the main resources available in the HP 12 C calculator, especially algebraic operations, involving percentage, interest, discounts, amortization and applicable resources to financial mathematics. The study also intends to contribute, with knowledge of financial mathematics from problem solving, using the HP 12 C calculator as a tool. This is a qualitative research, with intervention, and for that, the HP financial calculator was used. 12 C as a pedagogical tool for problem solving. Whit this strategy, the investigation proposed to prepare students for the exercise of citizenship, solving everyday situations, as well as subsidizing information and knowledge that may be useful in the job market. Basic concepts related to the proposed theme are presented to the research subjects, whit contextualized examples, specifying the main agents that facilitate the understanding of the conte